A Mendelian randomization study investigating the causal associations of 35 blood and urinary metabolite biomarkers with breast cancer development - Ting Lin; Yimin Liu; Zixuan Liu; Ao Liu; Runtong Liu; Qianchao Wang (Discover Oncology)
Abstract Breast cancer is the most common cancer among women worldwide. The present study utilized a bidirectional Mendelian randomization methodology to explore the causal associations between 35 blood and urinary metabolic markers and distinct subtypes of breast cancer. The MR-PRESSO method was employed to detect and correct for pleiotropic effects, with statistical significance adjusted using the false discovery rate (FDR). The findings revealed significant causal links between certain metabolic markers and specific breast cancer subtypes. Specifically, glucose (OR: −0.187; 95% CI: −0.344 to −0.030) and glycated hemoglobin (HbA1c) (OR: −0.150; 95% CI: −0.2498 to −0.051) were associated with benign breast cancer. In contrast, statin-adjusted apolipoprotein B (OR: 0.493; 95% CI: 0.029 to 0.957) and low-density lipoprotein (LDL) (OR: 0.550; 95% CI: 0.056 to 1.043), urinary sodium (OR: −3.138; 95% CI: −5.710 to −0.565), and triglycerides (OR: 0.606; 95% CI: 0.0824 to 1.129) were correlated with intraductal carcinoma in situ. Apolipoprotein A (OR: 0.178; 95% CI: 0.053 to 0.304) and high-density lipoprotein (HDL) cholesterol (OR: 0.159; 95% CI: 0.045 to 0.273) were linked to intraductal carcinoma in situ of the breast, while total protein (OR: 0.800; 95% CI: 0.181 to 1.409) and albumin (OR: 0.883; 95% CI: 0.255 to 1.512) were associated with lobular carcinoma in situ. In the reverse analysis, benign breast cancer (OR: 0.014; 95% CI: 0.002 to 0.026) exhibited a correlation with urinary creatinine, and intraductal carcinoma in situ (OR: 0.004; 95% CI: 0.001 to 0.007) with insulin-like growth factor 1 (IGF-1). This study identifies key biomarkers for breast cancer susceptibility and resistance, offering a scientific foundation for further research endeavors.